Emily Yodis: capstone - Yodis, Emily, artist (Colorado State University. Libraries, 2022)
The artist's statement: Every 7 years the body turns over every cell essentially creating a whole new body, a new person who looks, feels and acts differently. I am a completely different woman than I was at even 16 years old. In my life I have had a tumultuous relationship with my body and the concept of sex; specifically, intimacy and pleasure. I view this collection of work as a reclamation of bodily autonomy and understanding, helping me find love for a new body that has never seen such harsh criticism. Safety, comfort, ownership, reclamation, understanding, overcoming are all processes that I work through in life, but also within my metalwork. Mental power, sexual power, and physical strength/integrity are concepts I embed in the physical creations I produce. My jewelry is directly connected to the location of the body on which the piece is worn. It is in conversation with my ceramic work, which also references the body, but in an abject style. These vessels give the viewer an uneasy, uncomfortable, and even disgusted reaction. Social constructs about how some parts of the body are seen as beautiful while others (and sometimes even the same parts) are seen as disgusting fascinate me. I explore these ideas in my piece "The Beauty of Something Unbeautiful", in which I contrast couture-style jewelry with the less glamorous location of the foot. Femininity, sex from the female perspective, and stigma about attention and the act of "showing off" also interest me. My piece "Spineless" engages these themes through taking the central structure of the human body and displaying it in a more vulnerable position on the naked human back. The consistent theme within most of my metalwork is the reclamation of my own body. Growing up as a woman there was tons of pressure to fit the ideal body type, even though the ideal body type has changed so much just in the 23 years I have been alive. Making amends with my body has empowered me to finally accept not necessarily what I look like, but the idea that my body is a vessel that contains who I really am. This reconciliation has brought me peace and happiness, and helps ground my artmaking process. Finally coming to terms and accepting my physical form has been one of the most prominent struggles in my womanhood. Many women have gone through similar experiences as I. For me, the most important part of healing is channeling my experiences into the physical manifestation of objects that are both vulnerable and strong.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: jewelry; metalsmithing